The Threshold of External Debt Ratio in Indonesia - Siti Karimah; Nasrudin Nasrudin (INDEF - Institute for Development of Economics and Finance, 2020)
Since New Order1 regime, external debt has become one of the reliable capital sources in Indonesia. In 2017, the World Bank was incorporating Indonesia to the top ten middle-income country borrowers so it is necessary to analyze the effect of external debt ratio on economic growth. Using the debt Laffer curve theory, the authors determine the threshold of the external debt ratio. The method of analysis is quadratic regression. The research results indicate that there exists a non-linear relationship between the external debt ratio and economic growth in Indonesia. On the other hand, research results have found the threshold of external debt ratio in Indonesia is 48 per cent to Gross Domestic Product (GDP). The external debt ratio less than 48 per cent of GDP does not affect economic growth, but it will have a negative effect on economic growth when the ratio is more than 48 per cent of GDP. Keywords: external debt ratio, threshold, quadratic regression